PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TEHADAP KINERJA PEGAWAI PADA HOTEL NON BINTANG DI BANDUNG - Imas Komariyah (Quantitative Economics Journal, 2017)
This study aimed to analyze the effect of transformational leadership, organizational culture toward employee performance. Sampling in this study using a Stratified Random Sampling and the size of 92 respondents, methods of analysis use path Analysis. The results showed that based on the preception of respondents, the overall variable transformotional leadership in the category quite well toward good, look that variable tranformational leadership (X1) has a direct amount to 13,62%, indirect effect throught its realtionship culture organization (X2) amount to 11,30, and total the effect 24,92%. Culture organitation has a direct amount to 29,38%, indirect effect throught its relationship tranformational leadership 11,30% and total the effect 40,68%. The coefecient of determination calculation result is equal to 65,59%. The result of reseach concludes that there are partially and stimultaneously significanteffect of transformational leadership variable, organizational culture toward employee performance.